Extreme drought and sexual violence against adolescent girls and young women: A multi-country population-based study. - Lucas Hertzog; Marshall Makate; David Chipanta; Boladé Banougnin; Martina Mchenga; Gavin Pereira; Sylvester Dodzi Nyadanu; Jennifer Dunne; Paula S Tallman; Shalean Collins; Kefyalew Addis Alene; Pauline Rousseau-Gueutin; et al. (PLOS Global Public Health)
Droughts have profound and far-reaching impacts on human health and well-being, but their influence on sexual violence among adolescent girls in low- and middle-income countries (LMICs) is underexamined.This study examines the association between drought and sexual violence against adolescent girls and young women globally, using cross-sectional, nationally representative data from the Violence Against Children and Youth Surveys (VACS) from 2013 and 2019. The sample includes 35,309 females aged 13-24 from 14 countries in Central and South America, sub-Saharan Africa, Southeast Asia, and Eastern Europe. Sexual violence was defined based on unwanted sexual contact, completed or attempted forced penetration, and pressured sexual activity within the past 12 months. Drought exposure captured intensity and duration of drought conditions measured using the Global Standardized Precipitation-Evapotranspiration Index (SPEI) over a 48-month period before surveys. Bayesian Generalized Linear Models were employed to estimate the association between drought exposure and reported experiences of sexual violence, controlling for age, relationship status, school attendance, and wealth. The analysis revealed that exposure to prolonged and extreme drought, lasting 8-43 months in a 48-month period, was associated with higher odds of sexual violence (OR 1.21, 95% CI 1.21 to 1.22). Very dry periods are also associated with increased odds of experiencing sexual violence (OR 1.04, 95% CI 1.04 to 1.05). In contrast with extreme conditions, exposure to slight to moderate drought and recent and long periods suggested potential protective effects.This study provides novel evidence of an association between extreme drought and an increased likelihood of sexual violence against adolescent girls and young women in LMICs. The findings emphasise how climate change can exacerbate social vulnerabilities through its indirect effects, highlighting the need for comprehensive assessments of its impact on vulnerable populations.